Hemerobiidae from Deceit Island: the Southernmost Neuroptera in the Americas - Faúndez, Eduardo I.; Carvajal, Mariom A. (My University, 2022)
ABSTRACT The Neuropteran fauna on the most meridional part of South America is relatively scarce. Two families, Hemerobiidae and Coniopterigydae, have been recorded so far. Accordingly, only a few species have reached the south of Tierra del Fuego. Currently, the southernmost records of these species, Hemerobius chilensis Nakahara, 1965 and Megalomus flinti (Nakahara, 1965), are from Puerto Williams, Navarino Island (54°56′S 67°37′W), which makes them the southernmost distributed neuropterans in the continent. Here we provide the first records for two Neuroptera species, Hemerobius nekoi Monserrat, 1996 and Megalomus flinti; from Deceit Island, a remote subantarctic island within the Cape Horn archipelago (55°51′41″S 67°08′31″W). The records provided makes these species the southernmost recorded lacewings in the continent; extending the known distribution of neuropterans in South America nearly 110km towards the south.
Keywords: brown lacewings; faunistics; cape horn